EVALUASI KUALITAS LINGKUNGAN TERHADAP KEGIATAN LAPANGAN MIGAS TERBATAS PT TIARABUMI PETROLEUM KECAMATAN PENINJAUAN KABUPATEN OGAN KOMERING ULU - Sari, Enda Kartika; MZ, Lindawati (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2018)
PT Tiara Bumi Petroleum is one of the companies engaged in the oil and gas sector is one company that gives positive and negative impacts. PT Tiarabumi Petroleum has been in production since October 2014. The location of PT Tiarabumi Petroleum is around agricultural land and residential community located in Mandala and Peninjauan village of Kabupaten Ogan Komering Ulu. Population settlements are growing in Mandala Village and Peninjaun Village. Population settlements also began to develop in the South, West and East of the company location. This resulted in a mutually influencing environmental impact of both PT Tiarabumi Petroleum operational impact on the surrounding community and the impact of the settlement on the operation of PT Tiarabumi Petroleum. The method used in this research is survey and laboratory method. The survey method used in this study is descriptive qualitative, because the variables collected from the data will be analyzed and presented in the form of frequency, average number and other qualifications are descriptive statistically. Conclusions of environmental management and monitoring results by PT Tiarabumi Petroleum are 1) environmental management and monitoring has carried out environmental management obligations according to the direction of Environmental Management Plan (UKL) and Environmental Monitoring (UPL), but not yet optimal where the results of labratory analysis still have parameters which is still above the environmental quality standard of noise in the region Booster needs to get special attention, 2) Content of COD in the Ogan River has been seen since the initial hue that is already above the quality standards hinted. Since the operation of PT Tiarabumi Petroleum has never conducted the disposal of waste / pollutants into the river. Therefore, the government should monitor the quality of river water that can be generated from the community or the environment. Environmental parameters that are still above environmental standards for improved management include planting trees with small leafy types (bamboo) and making soundproofing room for Booster machines. In addition to the surrounding community should minimize pollutants into the river water, especially on domestic waste that arise from the community so that the content of BOD and COD in the water below the quality standard.